Non-motor effects of deep brain stimulation in Parkinson's disease motor subtypes. (April 2023) - Jost, Stefanie T.; Konitsioti, Agni; Loehrer, Philipp A.; Ashkan, Keyoumars; Rizos, Alexandra; Sauerbier, Anna; dos Santos Ghilardi, Maria Gabriela; Rosenkranz, Franz; Strobel, Lena; Gronostay, Alexandra; Barbe, Michael T.; Evans, Julian; et al.
Abstract: Introduction: Deep brain stimulation (DBS) is a well-established treatment for patients with Parkinson's disease (PD) improving quality of life, motor, and non-motor symptoms. However, non-motor effects in PD subtypes are understudied. We hypothesized that patients with 'postural instability and gait difficulty' (PIGD) experience more beneficial non-motor effects than 'tremor-dominant' patients undergoing DBS for PD. Methods: In this prospective, observational, international multicentre study with a 6-month follow-up, we assessed the Non-Motor Symptom Scale (NMSS) as primary and the following secondary outcomes: Unified PD Rating Scale-motor examination (UPDRS-III), Scales for Outcomes in PD (SCOPA)-activities of daily living (ADL) and -motor complications, PDQuestionnaire-8 (PDQ-8), and levodopa-equivalent daily dose (LEDD). We analysed within-group longitudinal changes with Wilcoxon signed-rank test and Benjamini-Hochberg correction for multiple comparisons. Additionally, we explored outcome between-group differences of motor subtypes with Mann-Whitney U-tests. Results: In 82 PIGD and 33 tremor-dominant patients included in this study, baseline NMSS total scores were worse in PIGD patients, both groups experienced postoperative improvements of the NMSS sleep/fatigue domain, and between-group differences in postoperative outcomes were favourable in the PIGD group for the NMSS total and miscellaneous domain scores. Conclusions: This study provides evidence of a favourable outcome of total non-motor burden in PIGD compared to tremor-dominant patients undergoing DBS for PD. These differences of clinical efficacy on non-motor aspects should be considered when advising and monitoring patients with PD undergoing DBS. Highlights: 6-month DBS outcomes compared in PIGD and tremor-dominant Parkinson's disease. PIGD: worse preoperative non-motor burden, ADL, motor complications, quality of life. PIGD: favourable outcome for total non-motor burden, ADL, and communication. Tremor-dominant patients: favourable outcome only for stigma. Different clinical efficacy in motor subtypes helps advising and monitoring patients.